Phylogenetic relationships and population structure of Ralstonia solanacearum isolated from diverse origins in Taiwan. (8th March 2014) - Lin, C.‐H.; Tsai, K.‐C.; Prior, P.; Wang, J.‐F.
<x xml:space="preserve">Abstract</x> Bacterial wilt caused by Ralstonia solanacearum is a destructive disease for many crops. The aim of this study was to investigate the phylogenetic relationships and genetic structure of an R. solanacearum population from diverse origins in Taiwan. All 58 tested isolates belonged to phylotype I, except the two biovar 2 isolates from potato. These belonged to phylotype IIB sequevar 1 and were identical to known potato brown rot strains, which were probably introduced. Phylotype I isolates were grouped into 10 sequevars. Sequevar 15 was predominant (34 out of 56 isolates). Its distribution covered the whole island and it was largely associated with solanaceous crops such as tomato, and with tomato field soil. A total of 14 haplotypes were identified based on a partial endoglucanase gene sequence. Parsimony network analysis revealed that haplotype A was the oldest haplotype in the local population. It encompassed all but one of the sequevar 15 isolates. Large variation in virulence on tomato was observed among the 58 isolates, and seven pathotypes were identified. Significant genetic differentiation was detected among pathotypes. Moreover, genetic differentiation was detected between biovar 3 and biovar 4 subgroups and between the strains associated with solanaceous and non‐solanaceous species, but none was detected between strains from different geographic origins. The results suggest that the phylotype I population in Taiwan is homogeneous, while mutation and local adaptation to specific ecological niches keep shaping the population.